Development of a simplified transmission line model directly in the phase domain - Silva, R. C. [UNESP]; Kurokawa, S. [UNESP]; Costa, E. C M; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A transmission line digital model is developed direct in the phase and time domains. The successive modal transformations considered in the three-phase representation are simplified and then the proposed model can be easily applied to several operation condition based only on the previous knowing of the line parameters, without a thorough theoretical knowledge of modal analysis. The proposed model is also developed based on lumped elements, providing a complete current and voltage profile at any point of the transmission system. This model makes possible the modeling of non-linear power devices and electromagnetic phenomena along the transmission line using simple electric circuit components, representing a great advantage when compared to several models based on distributed parameters and inverse transforms. In addition, an efficient integration method is proposed to solve the system of differential equations resulted from the line modeling by lumped elements, thereby making possible simulations of transient and steady state using a wide and constant integration step. © 2012 IEEE.
Keywords: lumped elements; state equations; Transmission line modeling; transmission line theory; Circuit components; Digital model; Distributed parameter; Electromagnetic phenomena; Integration method; Line parameters; Lumped element; Modal transformation; Operation conditions; Phase domain; Power devices; State equations; Steady state; System of differential equations; Time domain; Transmission line models; Transmission systems; Voltage profile; Differential equations; Electric lines; Electric power transmission; Inverse transforms; Knowledge representation; Modal analysis; Transmission line theory